Effective Use of Apparatotherapy in the Rehabilitation after Anterior Cruciate Ligament Arthroscopic Reconstruction - Alexey O. Pavlov; Elena Y. Mozheyko; Semyon V. Prokopenko; Evgeniy V. Portnyagin; Alexey D. Streltsov; Mikhail A. Chistov; Maria A. Khramchenko (Вестник восстановительной медицины, 2022)
Anterior cruciate ligaments’ rupture is a frequent injury among young and physically active people, leading to temporary disability.There is no specifically regulated set of physical exercises for this category of patients, there are no recommendations for the use ofapparatotherapy techniques.Aim. Evaluation of apparatotherapy effectiveness use in combination with therapeutic physical exercises at the early stage of recoverytreatment after anterior cruciate ligament (ACL) reconstruction.Material and methods. 30 patients were examined on the basis of the Center for Physical Rehabilitation of the Federal Medical andBiological Agency of Russia after reconstruction of the ACL. They were divided into 3 groups of 10 people. The patients of the first groupunderwent rehabilitation with the use of rehabilitation exercises and physiotherapy. Patients of the second and the third groups wereadditionally treated with apparatotherapy on the “Artromot” device. Patients of the third group were additionally given sessions onthe “Con-trex Multi Joint” simulator. The duration of follow-up was 8 weeks for each patient. In all groups, the following were used forevaluation: visual-analog pain scale, “Lysholm” and “IKDL” scales, clinical examination (Lachman test, measurement of the lower limbcircumference).Results and discussion. The study revealed a statistically significant difference in the increase in the indicators of the “IKDL” and“Lysholm” scales, the decrease in the indicator of the visual-analog pain scale in patients of the second and third groups, compared topatients of the first group (p<0.05).Further monitoring is necessary with isokinetic tests for the thigh and lower leg muscles in order to assess the speed and strengthindicators of these muscle groups when evaluating the apparatotherapy effect on the long-term results of rehabilitation treatment.Conclusion. The algorithm of restorative treatment after ACL arthroscopic reconstruction with the use of apparatotherapy on“Artromot” and “Con-Trex Multi Joint” devices in combination with rehabilitation exercises and physiotherapy is more effectivecompared to similar treatment without apparatotherapy.